Pengaruh Bauran Promosi, Harga dan Kualitas Produk Terhadap Kepuasan Pelanggan Kartu Internet Digital By.U Pada PT. Telkomsel Banda Aceh - Isthafan Najmi; Moch Syauki; Haryoka Haryoka; Yuni Ayu Safitri (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The purpose of this research is to determine the simultaneous influence of the promotion mix, price and product quality on customer satisfaction with Digital by.U internet card users at PT. Telkomsel Banda Aceh. This research was conducted on Digital by.U internet card users at PT. Telkomsel Banda Aceh, while the object of this research is the promotion mix, price, product quality and customer satisfaction with a selected sample of 98 people. The data analysis equipment in this research uses a Likert scale and multiple linear regression data analysis. The research results show that the promotion mix, price and product quality together have a significant effect on customer satisfaction with Digital by.U internet card users at PT. Telkomsel Banda Aceh obtained Fcount > Ftable (67.780 > 2.701) at a significance level of 0.000, then the research results also prove that the individual promotion mix has a significant effect on customer satisfaction for users of the Digital by.U internet card at PT. Telkomsel Banda Aceh with a regression coefficient value of 0.160 with a significance level of 0.000. The research results also prove that price, individually, has a significant effect on customer satisfaction with Digital by.U internet card users at PT. Telkomsel Banda Aceh with a regression coefficient value of 0.112, with a significance level of 0.004 and individual product quality has a significant effect on customer satisfaction with a regression coefficient value of 0.157 with a significance value of 0.000 at a = 5%. It is hoped that the results of this research will be useful for PT. Telkomsel Banda Aceh to be able to further increase customer satisfaction in the future.